2010
DOI: 10.1111/j.1464-5491.2010.03047.x
|View full text |Cite
|
Sign up to set email alerts
|

The high prevalence of malnutrition in elderly diabetic patients: implications for anti‐diabetic drug treatments

Abstract: Malnutrition is highly prevalent in elderly diabetic inpatients and, paradoxically, contributes to 'good' glycaemic control. Malnutrition should be screened for in these patients and, when present, should prompt a revision in diet and drug therapy. In particular, the possibility of reducing unnecessary drug therapy should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 27 publications
3
50
3
2
Order By: Relevance
“…18,[36][37][38] Also, low levels of glycaemia may not always be indicative of intentional good glycaemic control, but rather a proxy for poor nutritional status and general frailty, both of which have been associated with increased mortality risk. 39 The latter is supported by the existence of a J-shaped association between levels of glycaemia and mortality risk in non-diabetic populations, suggesting that non-glycaemic factors may partly explain the observed risk in the lower glycaemic range. 40 In terms of glycaemic variability, our results are in accordance with previous studies that have shown that higher variability in HbA1c is associated with an increased risk of mortality in patients with T2D.…”
Section: Discussionmentioning
confidence: 91%
“…18,[36][37][38] Also, low levels of glycaemia may not always be indicative of intentional good glycaemic control, but rather a proxy for poor nutritional status and general frailty, both of which have been associated with increased mortality risk. 39 The latter is supported by the existence of a J-shaped association between levels of glycaemia and mortality risk in non-diabetic populations, suggesting that non-glycaemic factors may partly explain the observed risk in the lower glycaemic range. 40 In terms of glycaemic variability, our results are in accordance with previous studies that have shown that higher variability in HbA1c is associated with an increased risk of mortality in patients with T2D.…”
Section: Discussionmentioning
confidence: 91%
“…30 g/L, occurrence of malnutrition was particularly frequent (53%) in patients with T2DM in a geriatric ward. 29 The high prevalence of malnutrition was not different between obese elderly patients and other older patients. In another geriatric ward study, 20 the mean serum albumin concentration of patients with T2DM was also particularly low (mean 32 g/L; standard deviation [SD] ± 5.0).…”
Section: Nutritional Issuesmentioning
confidence: 97%
“…Malnutrition leads to poor health outcomes, sarcopenia, increased risk of falls, inflammation and frailty syndrome (Johansson et al, 2008;Cruz-Jentoft et al, 2010). Malnutrition might modify the pharmacokinetic and pharmacodynamics of drugs which has to be considered in the treatment of older adults (Vischer et al, 2010).…”
Section: Dehydration and Malnutritionmentioning
confidence: 99%